Analysis of Sociodemographic Determinants of Not In Employment, Education, or Training (NEET) in Maluku Province - Utami, Regina Pramesti; Pratomo, Devanto Shasta (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
In a strategic effort to fully realize the potential of its demographic bonus, Indonesia is committed to the qualitative enhancement of its young populace by creating expansive opportunities in employment, education, and skill development. This initiative is directly aligned with SDGs Target 8.6, which aims to reduce the proportion of youth who are Not in Employment, Education, or Training (NEET). Although extensive research on NEET has been conducted, there has been no specific study identifying the sociodemographic determinants of NEET in Maluku Province, which had the highest percentage in Indonesia in 2023. This study aims to fill that gap by using secondary data from the August 2023 National Labor Force Survey. The analysis was conducted using binary logistic regression, examining the relationship between NEET status as the dependent variable and independent variables such as age, gender, marital status, disability, education level, regional classification, and migrant status. The results indicate that individuals aged 20-24, females, those with a history of marriage, persons with disabilities, those with senior high school education or higher, and those living in rural areas have a greater probability of being NEET. Conversely, migrant youth show a lower tendency to fall into this category. These findings are expected to serve as a basis for the Maluku Provincial Government in formulating more targeted policies to increase the participation of young people.